Fabrication of well-miscible and highly enhanced polyethylene/ultrahigh molecular weight polyethylene blends by facile construction of interfacial intermolecular entanglement - Buyong Wu (Elsevier, 2021)
To enhance the interfacial intermolecular entanglement of the polyethylene/ultrahigh molecular weight polyethylene (PE/UHMWPE) system, the blend was fabricated via a facile melt blending process in presence of UHMWPE with relatively low molecular weight (LUHMWPE). Incorporation of LUHMWPE filled molecular weight gap between PE and UHMWPE, and thus a matched viscosity gradient for the components of blend was constructed. The UHMWPE/LUHMWPE particles with remarkably decreased size and distribution were tightly embedded in PE matrix, and the interface transition area between UHMWPE and PE phase increased dramatically. Meanwhile the molecular entanglement density and viscoelasticity were improved greatly, demonstrating enhanced interfacial adhesion, interfacial intermolecular diffusion and construction of a dense chain entanglement network in blend. An obvious deformation accompanied by lots of pulling-out UHMWPE fibrils was observed on the fractured surfaces of the blend, and the mechanical property was highly enhanced by a roughly 38%/22% increase in tensile strength and a great improvement in impact strength, respectively when compared with neat PE and PE/UHMWPE. The blend was further employed to fabricate pipes, which exhibited significantly improved tensile strength both along hoop and axial direction, and the internal pressure resistance. This work provides a facile method for manufacturing PE/UHMWPE blend and pipe with promising application potentials.